2015
DOI: 10.1021/acs.chemrestox.5b00055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Fates of DNA Adducts in Adipocytes Post-sulfur Mustard Exposure in Vitro and in Vivo Using a Simultaneous UPLC-MS/MS Quantification Method

Abstract: Sulfur mustard (SM) is a powerful alkylating vesicant that can rapidly penetrate skin, ocular, and lung bronchus mucous membranes and react with numerous nucleophiles in vivo. Although the lesion mechanisms of SM remain unclear, DNA damage is believed to be the most crucial factor in initiating SM-induced toxicity. Four major DNA adducts were identified for retrospective detection and DNA lesion evaluation, namely, N(7)-[2-[(2-hydroxyethyl)thio]-ethyl]guanine (N(7)-HETEG), bis(2-ethyl-N(7)-guanine)thioether (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…56 Wang et al reported that the SM (100 μ M) also forms the structurally related N7-[2-[(2-hydroxyethyl)thio]ethyl]-guanine (N7-HETEG) and bis[2-(guanin-7-yl)ethyl]-sulfide (Bis-G), among other adducts, as the biomarkers for DNA damage in rodents and human keratinocytes, hepatocytes and lung fibroblasts. 64 Very high levels N7-HETEG and G-SM-G cross-link (> 4 adducts per 10 5 bases) were formed in all cell lines. The t 1/2 values of N7-HETEG and its cross-link showed no significant differences among the liver, lungs, and skin-derived cells.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…56 Wang et al reported that the SM (100 μ M) also forms the structurally related N7-[2-[(2-hydroxyethyl)thio]ethyl]-guanine (N7-HETEG) and bis[2-(guanin-7-yl)ethyl]-sulfide (Bis-G), among other adducts, as the biomarkers for DNA damage in rodents and human keratinocytes, hepatocytes and lung fibroblasts. 64 Very high levels N7-HETEG and G-SM-G cross-link (> 4 adducts per 10 5 bases) were formed in all cell lines. The t 1/2 values of N7-HETEG and its cross-link showed no significant differences among the liver, lungs, and skin-derived cells.…”
Section: Discussionmentioning
confidence: 89%
“…The chemistry and reactivity of nitrogen 8-10, 18, 20, 24, 47-56 and sulfur 44, 57-64 mustards with nucleosides and DNA in vitro is well studied. There are also numerous studies that examine the mustard derived DNA adducts from treated cell culture and animals, 46,48,50,54,56,59,64,65 including white blood cells of patients on chemotherapeutic regimens that include a nitrogen mustard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up studies focused on urinary excretion of metabolites and adduct distributions in different rodent organs (Yue et al 2015;Zhang et al 2014). In addition, these authors analyzed adduct levels in adipocyte cell lines and adipose tissue, suggesting a depot effect of SM in lipidrich environments (Wang et al 2015).…”
Section: N7-hete-guamentioning
confidence: 99%
“…Despite this, SM was broadly used in the Iran-Iraq War (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988) and even recently in asymmetric conflicts, such as in Syria and Iraq (Dons 2013;OPCW 2017;Thiermann et al 2013). Due to ease of chemical synthesis as well as potentially undestroyed residual stockpiles in conflict areas, it may also be accessible for terroristic groups (Balali-Mood and Hefazi 2005;Wang 2010). Therefore, SM still represents a realistic threat, both for civilians and soldiers, which calls for reliable, specific, and sensitive exposure assessment.…”
Section: Introductionmentioning
confidence: 99%